Self-efficacy centered comprehensive interventions and effects in patients undergoing radical surgery for gastric cancer - Zhou, Huali; Bao, Rong; Qiu, Liping; Zhang, Yuhan; Gu, Qiong (Frontiers in Medicine, 2025)
ObjectiveTo assess the effects of self-efficacy theory centered comprehensive interventions on perioperative nutritional status, self-management ability, self-efficacy perception, and quality of life in patients undergoing radical surgery for gastric cancer.MethodsUsing a convenience sampling method, 213 patients who underwent radical gastrectomy for gastric cancer at a tertiary specialized hospital in Sichuan Province from October 2023 to April 2024 were selected as the research subjects for randomized controlled trial. The selected patients were randomly assigned to the experimental group with 107 cases and the control group with 106 cases. The experimental group received self-efficacy centered comprehensive interventions including dietary guidance, psychological intervention and counseling, symptom management, exercise guidance, etc. The control group received routine medical interventions. The nutritional status, self-efficacy, self-management ability, and quality of life of the two groups of patients were evaluated at 1 month, 3 months, 6 months, and 1 year after discharge from hospital.ResultsThe analytical outcomes across diverse time intervals demonstrated that the nutritional risk of patients in the experimental group was significantly lower than that in the control group, while the self-efficacy scale, self-management ability scale, and quality of life scores in the experimental group were all higher than those in the control group. The differences were statistically significant (p < 0.05).ConclusionComprehensive interventions centered on self-efficacy theory can improve the nutritional status, self-efficacy, self-management ability, and quality of life of patients undergoing radical gastrectomy for gastric cancer.